Blocking H1/H2 histamine receptors inhibits damage/fibrosis in Mdr2–/– mice and human cholangiocarcinoma tumorigenesis. Issue 3 (1st June 2018) - Kennedy, Lindsey; Hargrove, Laura; Demieville, Jennifer; Karstens, Walker; Jones, Hannah; DeMorrow, Sharon; Meng, Fanyin; Invernizzi, Pietro; Bernuzzi, Francesca; Alpini, Gianfranco; Smith, Steven; Akers, Austin; et al.
Abstract : Primary sclerosing cholangitis (PSC) patients are at risk of developing cholangiocarcinoma (CCA). We have shown that (1) histamine increases biliary hyperplasia through H1/H2 histamine receptors (HRs) and (2) histamine levels increase and mast cells (MCs) infiltrate during PSC and CCA. We examined the effects of chronic treatment with H1/H2HR antagonists on PSC and CCA. Wild‐type and multidrug‐resistant knockout (Mdr2 –/– ) mice were treated by osmotic minipumps with saline, mepyramine, or ranitidine (10 mg/kg body weight/day) or a combination of mepyramine/ranitidine for 4 weeks. Liver damage was assessed by hematoxylin and eosin. We evaluated (1) H1/H2HR expression, (2) MC presence, (3) L‐histidine decarboxylase/histamine axis, (4) cholangiocyte proliferation/bile duct mass, and (5) fibrosis/hepatic stellate cell activation. Nu/nu mice were implanted with Mz‐ChA‐1 cells into the hind flanks and treated with saline, mepyramine, or ranitidine. Tumor growth was measured, and (1) H1/H2HR expression, (2) proliferation, (3) MC activation, (4) angiogenesis, and (5) epithelial–mesenchymal transition (EMT) were evaluated. In vitro, human hepatic stellate cells were evaluated for H1HR and H2HR expression. Cultured cholangiocytes and CCA lines were treated with saline, mepyramine, or ranitidine (25 μM) before evaluating proliferation, angiogenesis, EMT, and potential signaling mechanisms. H1/H2HR and MC presence increased in human PSC and CCA. In H1/H2HR antagonist (alone or in combination)–treated Mdr2 –/– mice, liver and biliary damage and fibrosis decreased compared to saline treatment. H1/H2HR antagonists decreased tumor growth, serum histamine, angiogenesis, and EMT. In vitro, H1/H2HR blockers reduced biliary proliferation, and CCA cells had decreased proliferation, angiogenesis, EMT, and migration. Conclusion : Inhibition of H1/H2HR reverses PSC‐associated damage and decreases CCA growth, angiogenesis, and EMT; because PSC patients are at risk of developing CCA, using HR blockers may be therapeutic for these diseases. (Hepatology 2018).